ナンキョク ショウワキチ シュウヘンイキ ニオケル VHF/UHF ツウシン カンド ソクテイ - 氏家, 宏之; ウジイエ, ヒロユキ; 木津, 暢彦; キヅ, ノブヒコ; Ujiie, Hiroyuki; Kizu, Nobuhiko (2003)
P(論文) 海氷上を含めた昭和基地南方沿岸域と昭和基地間のVHF/UHF帯の通信状態を調査した.現場で利用している機器の地域による特性が得られ,VHFとUHF通信に関して感度良好な地点と悪い地点が明確となった.この結果は,この地域の調査隊にとって有効な情報となるだろう. The sensitivity of radio communication for VHF/UHF bands was checked on the sea ice and the coastal regions in the southern regions of Syowa Station. The measurement was carried out by the Communications equipments actually used during the field observation and the sensitivities on measuring points clarified. The result of UHF and VHF bands will be useful for field party in that area. departmental bulletin paper